A Potential Study of Automation System in Industrialised Building System (IBS) in Enhancing Malaysian Construction Industry’s Performance - Siti Azira, Abd Rahim*; Mohd Amir Shazwan, Hashim*; Wong, Sook Shen (INTI International University, 2020)
Automation is one of the advanced technologies which can be used for improving the efficiency and performance of construction projects in various aspects of the construction industry. Although the introduction of automation technologies can enhance efficiency, many manufacturers of the Malaysian Industrialized Building System (IBS) do not support the presence of automation technology. Construction-related IBS problems such as declining efficiency and productivity, labour shortages, weak occupational safety, and unsafe working environment have hindered the implementation of IBS in Malaysia, but have opened up opportunities for more practical ideas within the industry. Another prospective choice is to implement advanced building technology such as automation through the IBS, which has the potential to enhance the industry in terms of efficiency, protection, and quality and IBS adoption rate in Malaysia. Automation means replacement of human labours by machines; or the operation of a machine or device automatically, or remote control which enhanced productivity, quality and also reduce human efforts. This paper study on the potential implication of Automation through IBS in enhancing Malaysian construction industry’s performance. In order to achieve research goals, qualitative method is adopted which is through in-depth interview with industry experts. Content analysis and descriptive statistic is used to explore and categorize the opinions from professionals. The result is expected to provide a clearer understanding of the current construction problems facing the industry without the implementation of the Automation system in IBS, other than as a guidance for contractors to enhance their current approach and practise.